EFFECT OF TAX AUDIT ON GOVERNMENT REVENUE GENERATION IN LAGOS STATE - Johnson Olugbenga Agbede (Malete Journal of Accounting and Finance, 2024)
This study investigates the impact of tax audits on revenue generation in Lagos State, Nigeria, focusing specifically on the revenue from Pay-As-You-Earn (PAYE) and Direct Assessment (DA) over a 12-year period (2012-2023). Utilizing a longitudinal research design, data was sourced from the Lagos State Internal Revenue Service (LIRS) audit division. The methodology involved descriptive and inferential analysis, including ordinary least squares regression analysis, to explore the relationships between tax audits and revenue outcomes. Results indicate that tax audits positively and significantly influence both PAYE and DA revenues, with coefficients of 0.557 and 0.580, respectively. The study further highlights the significance of time as a variable influencing direct assessments, underscoring the cumulative effect of taxpayer compliance over years. The findings contribute to existing literature by elucidating the role of tax audits in enhancing revenue collection, providing valuable insights for tax authorities and policymakers. Recommendations for periodic tax audits to optimize revenue generation are offered, along with suggestions for future research to broaden the scope of inquiry in the field of taxation